Sociolinguistic research application and impact - Lawson, Robert; Sayers, Dave (Routledge, Taylor & Francis Group, 2016)
With chapters spanning research across five continents, Sociolinguistic Research: Application and Impact is essential reading for sociolinguistic researchers, students embarking on sociolinguistic research, and anyone interested in the practical application of research on language and society.